Determination of buprenorphine, norbuprenorphine, naloxone, and their glucuronides in urine by liquid chromatography–tandem mass spectrometry. Issue 9 (3rd June 2021) - Mariottini, Claudia; Gergov, Merja; Ojanperä, Ilkka
Abstract: A liquid chromatography–tandem mass spectrometry method for the simultaneous quantification of buprenorphine (BUP), norbuprenorphine (NBUP), naloxone (NAL), and their glucuronide conjugates BUP‐G, NBUP‐G, and NAL‐G in urine samples was developed. The method, omitting a hydrolysis step, involved non‐polar solid‐phase extraction, liquid chromatography on a C18 column, electrospray positive ionization, and mass analysis by multiple reaction monitoring. Quantification was based on the corresponding deuterium‐labelled internal standards for each of the six analytes. The limit of quantification was 0.5 μg/L for BUP and NAL, 1 μg/L for NAL‐G, and 3 μg/L for NBUP, BUP‐G, and NBUP‐G. Using the developed method, 72 urine samples from buprenorphine‐dependent patients were analysed to cover the concentration ranges encountered in a clinical setting. The median (maximum) concentration was 4.2 μg/L (102 μg/L) for BUP, 74.7 μg/L (580 μg/L) for NBUP, 0.9 μg/L (85.5 μg/L) for NAL, 159.5 μg/L (1370 μg/L) for BUP‐G, 307.5 μg/L (1970 μg/L) for NBUP‐G, and 79.6 μg/L (2310 μg/L) for NAL‐G. Abstract : Median and maximum concentrations of buprenorphine (BUP), norbuprenorphine (NBUP), naloxone (NAL), buprenorphine‐glucuronide (BUP‐G), norbuprenorphine‐glucuronide (NBUP‐G), and naloxone‐glucuronide (NAL‐G) were encountered in 72 urine samples from buprenorphine‐dependent patients.